L'installation en mouvement : une esthétique de la violence - Morosoli, Joëlle (Trois-Rivières : Editions d'Art Le Sabord, 2007)
Bourgeois, Louise ; Burden, Chris ; Fischli & Weiss ; Garrin, Paul ; Horn, Rebecca ; Kantor, Istvan ; Nitsch, Hermann ; Orlan ; Rist, Pipilotti ; Shaw, Jeffrey ; Stelarc ; Viola, Bill
Bibliog. p. 233-237
Frans
boek